Ethylene regulates peel spotting in fruit of cv. Sucrier banana (Musa acuminata, AA Group): Dependence on ripening stage - Mongkolchaiyaphruek, Anchaya; Wisutiamonkul, Apinya; Ketsa, Saichol (Agriculture and Natural Resources, 2023)
Importance of the work: Ethylene can induce banana ripening. Therefore, ethylene may be involved in the development of peel spotting in bananas. Objectives: To test the effect of ethylene on peel spotting in bananas (cv. Sucrier) in two stages of development. Materials & Methods: In the first study, fruits ripened to stage 3 (light green-yellow) were placed in airtight plastic containers and manipulated using carbon dioxide scrubber or ethylene absorbent, or both. In the second and third studies, fruit ripened to either stage 1 (green) or stage 3 were exposed to ethylene or 1-methylcyclopropene (1-MCP). Changes in spotting were monitored. Results: Removal of carbon dioxide or ethylene, or both had no significant effects on peel spotting of fruit in stage 3 (light green-yellow skin color) whereas spotting was reduced by ethylene during stage 1 (green skin color) but fruit in stage 3 was not affected. The 1-MCP treatment had no effect on peel spotting of fruit in stage 3, but in stage 1 fruit, the 1-MCP treatment clearly delayed the early development of the disorder. Main finding: The development of peel spotting in the early stage of fruit ripening in this cultivar was regulated differently by endogenous and exogenous ethylene. In contrast, the development of peel spotting in stage 3 or later was independent of endogenous ethylene.